2015
DOI: 10.1007/s11837-015-1336-5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dextran Coatings on the Cytotoxicity Properties of Ceria Nanoparticles Toward Bone Cancer Cells

Abstract: Cerium oxide nanoparticles have demonstrated great potential as antioxidant and radioprotective agents for nanomedicine applications especially for cancer therapy. The surface chemistry of nanoparticles is an important property that has a significant effect on their performance in biological applications including cancer diagnosis, cancer treatment, and bacterial infection. Recently, various nanosized cerium oxide particles with different types of polymer coatings have been developed to improve aqueous solubil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 27 publications
(79 reference statements)
0
12
0
1
Order By: Relevance
“…From this result, it has been found that nanoceria had the ability of free-radical scavenging, which created a precedent of nanoceria in biological applications and greatly inspired the people of research interest. Until now, there have been many studies on the toxicity properties of nanoceria coated with polymers (dextran, PEG, chitosan, heparin, PAA, and PVP) within the range of 3-20 nm as demonstrated in Figure 4 against cancer cells (lung, breast, ovary, osteosarcoma, and pancreas) and healthy cells (dermal fibroblasts, endothelial cell, keratinocytes, human monocytes, and macrophages) [25][26][27][28][29]. All these researches have laid a foundation for study of antioxidant property.…”
Section: Controllable Synthesis Of Nanoceriamentioning
confidence: 99%
“…From this result, it has been found that nanoceria had the ability of free-radical scavenging, which created a precedent of nanoceria in biological applications and greatly inspired the people of research interest. Until now, there have been many studies on the toxicity properties of nanoceria coated with polymers (dextran, PEG, chitosan, heparin, PAA, and PVP) within the range of 3-20 nm as demonstrated in Figure 4 against cancer cells (lung, breast, ovary, osteosarcoma, and pancreas) and healthy cells (dermal fibroblasts, endothelial cell, keratinocytes, human monocytes, and macrophages) [25][26][27][28][29]. All these researches have laid a foundation for study of antioxidant property.…”
Section: Controllable Synthesis Of Nanoceriamentioning
confidence: 99%
“…However, earlier studies from our group showed that the amount of dextran has an impact on the shape, stability, and cytotoxicity of the particles. Particles with a 0.1 M dextran coating were spherical in shape with longer stability and had higher toxicity against bone cancer cells in comparison to a 0.01 M dextran coating33. Further investigation on their effect on healthy bone cells revealed that they had minimal toxicity against osteoblasts5.…”
mentioning
confidence: 96%
“…8,9 However, CONPs show great tendency for agglomeration due to the high number of oxygen vacancies on their surface, leading to low stability of their water suspensions, which is the main restriction for their application. 10 This problem could be reduced by coating the CONPs with polymers, thereby improving their suspension stability.…”
Section: Introductionmentioning
confidence: 99%
“…In general, for coating CONPs, polymers such as dextran, 4,6,[10][11][12][13][14][15] heparin, 1,16 chitosan, 5,17 poly(ethylene glycol) (PEG), 18,19 and poly(lactic-co-glycolic acid) (PLGA) 20 are commonly used, as well as glucose, 21 citric acid and citrates, [22][23][24] and even drugs. 25 In selecting a polymer, attention should be paid to the type and amount of polymer coated over the nanoparticles, which would affect suspension stability.…”
Section: Introductionmentioning
confidence: 99%